Neuropharmacology of human TERA2.cl.SP12 stem cell-derived neurons in ultra-long-term culture for antiseizure drug discovery - Salmanzadeh, Hamed; Poojari, Ankita; Rabiee, Atefeh; Zeitlin, Benjamin D.; Halliwell, Robert F. (Frontiers in Neuroscience, 2023)
Modeling the complex and prolonged development of the mammalian central nervous system in vitro remains a profound challenge. Most studies of human stem cell derived neurons are conducted over days to weeks and may or may not include glia. Here we have utilized a single human pluripotent stem cell line, TERA2.cl.SP12 to derive both neurons and glial cells and determined their differentiation and functional maturation over 1 year in culture together with their ability to display epileptiform activity in response to pro-convulsant agents and to detect antiseizure drug actions. Our experiments show that these human stem cells differentiate in vitro into mature neurons and glia cells and form inhibitory and excitatory synapses and integrated neural circuits over 6–8 months, paralleling early human neurogenesis in vivo; these neuroglia cultures display complex electrochemical signaling including high frequency trains of action potentials from single neurons, neural network bursts and highly synchronized, rhythmical firing patterns. Neural activity in our 2D neuron–glia circuits is modulated by a variety of voltage-gated and ligand-gated ion channel acting drugs and these actions were consistent in both young and highly mature neuron cultures. We also show for the first time that spontaneous and epileptiform activity is modulated by first, second and third generation antiseizure agents consistent with animal and human studies. Together, our observations strongly support the value of long-term human stem cell-derived neuroglial cultures in disease modeling and neuropsychiatric drug discovery.